PREDICTIVE VALIDITY OF THE GEOGRAPHY FIELD PROJECT SCORE ON STUDENTS’ PERFORMANCE IN THE GEOGRAPHY THEORY IN CHOMA, ZAMBIA - Awoniyi, Samuel A.; Mike, Muleya Maxon (European Scientific Journal, ESJ, 2013)
﻿﻿﻿The study investigated the predictive validity of students’ scores in Geography Field Project on their final scores in Geography Theory examination. The predictors were Geography Field Project in terms of Observation, Recording and Interpretation while the criterion was the score in the final Theory examination in Geography. This study was an ex-post facto type of the descriptive research design because all the variables used had already occurred and therefore were not manipulated. The population consisted of all the grade twelve students from all the thirteen High Schools in Choma District, Zambia, who sat for the Geography examinations in the years 2009, 2010 and 2011. The population for the study consisted of all the 1950 students who sat for Geography examination in all the schools in the years under study. Seven hundred and eighty (780) students were selected and used for the study. The only research instrument used was a format designed for recording all necessary information in respect of students used for the study. The data collected were analysed using the descriptive statistics, regression analysis, Analysis of Variance and multiple comparison. The study revealed that students’ performance in Geography Field Project and Geography Theory final Examinations were on the average. Geography Field Project in terms of Interpretation and Observation accounted for 79.7% variance in students’ performance in Geography Theory Examination. Interpretation accounted for 79.6% while Observation accounted for 0.1%. The positive beta value shows that the more students were able to interpret and carry out observations; the better was their performance in Geography Theory Examinations. The overall mean score in Geography Field Project accounted for 79.7% variance in performance in Geography Theory Examination. The positive beta value of .560 indicated that the more students performed in Geography Field Project, the better their performance in Geography Theory Examination. There is no significant difference in the performance of students in Geography Final Examination Scores according to year of examination. It was however observed that there was a continuous decline in performance of students from 2009 through 2011.